Propostas de melhorias nos processos administrativos de uma empresa construtora a partir da aplicação do lean office - Cruz, Lídyci Thatielle Gurgel (2012)
The insertion of lean in construction together with its benefits arises the corporate interest in adopting the lean philosophy in the office, which is called lean office. The extermination of the existing waste and defining improvements in office focused on flows of document, process and information related to customers are challenges to achieving these improvements. Furthermore, most companies have little knowledge regarding their administrative processes what makes it difficult to diagnose activities that do not add value, culminating in the questioning of "how to minimize the waste generated in the administrative area of construction companies?". Faced with this problem, this paper aims to propose improvements in administrative processes of a construction company in the light of lean thinking philosophy. Furthermore, it also aims to critically analyze these processes mapped streams in search of waste; elaborate Value Stream Mapping (VSM) for future state and analyze the interfaces between administrative sectors mapped. To obtain these goals, the methodology used was divided into three steps: choose the value stream, study case and data analysis. The choice of the value stream comprises the definition of the administrative sectors of the company that would be studied, namely supply, maintenance, finance, accounting and human resources. Since the study case was divided into five phases: formulation of Value Stream Mapping (VSM) in the current state of the chosen sectors, identifying lean metrics which would be able to demonstrate the impact of efforts to implement the improvements, study of the interface between these administrative sectors, validation of the proposals for improvements and drafts of VSMs in the future state. Data analysis consisted of VSMs in current state and sources of evidence used, the diagnosis of the waste in processes and their respective classifications and analysis of proposals suggested improvements that could optimize the flow of sectors. Furthermore, the interface of mapped sectors was also analyzed. The research findings point to the choice of five administrative departments, namely supplies, maintenance, finance, accounting and human resources. For each sector a VSM was prepared in current and future states identifying theirs losses and ratings and the proposed improvements can demonstrate effectiveness through estimation of Task Accomplishment Times (TATs) and Permanence length (PL). Finally, we designed a generalized VSM involving all sectors, which enabled to illustrate how interaction between departments and key information exchanged between them in one sketch